2015
DOI: 10.1080/07315724.2014.919541
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of a Novel, Water-Soluble Undenatured Type II Collagen (NEXT-II)

Abstract: These results demonstrate the broad-spectrum safety and efficacy of NEXT-II in ameliorating the symptoms of arthritis. Key Teaching Points: •A novel, water-soluble, undenatured type II collagen (NEXT-II) was developed for osteoarthritis. •The safety studies including acute oral and dermal toxicity, primary dermal and primary eye irritation, Ames' bacterial reverse mutation assay, mouse lymphoma assay, and 150-day long-term safety studies were conducted. •NEXT-II exhibited significant efficacy in ameliorating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…It was reported that UC-II supplementation does not affect the NF-κB levels in human synovial MH7A cells. However, in another study, it was shown that UC-II supplementation regulates the NF-κB pathway-related markers (26,38).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was reported that UC-II supplementation does not affect the NF-κB levels in human synovial MH7A cells. However, in another study, it was shown that UC-II supplementation regulates the NF-κB pathway-related markers (26,38).…”
Section: Discussionmentioning
confidence: 95%
“…However, we showed that UC-II inhibits NF-κB, TNF-α, IL-1β, IL-6, COX-2, and IKK-γ in MIA induced OA rats. Similarly, UC-II supplementation reduced the serum IL-1β, IL-6, and IL-8 and TNF-α levels in collageninduced arthritis (26,38). In addition, in the case of osteoarthritis defined by a subclinical immune disorder and the vicious cycle of inflammatory events, UC-II promoted a reduction in inflammation (10).…”
Section: Discussionmentioning
confidence: 99%
“…This means that active UC-II supplementation alone (10 mg/day for 150 days) was well tolerated and increased the well-being significantly in moderately arthritic dogs [74]. Another water-soluble UC-II form also exhibited similar noteworthy efficiency in relieving pain and inflammation in collagen-induced arthritis in mice, as well as moderately arthritic dogs after 150 days of supplementation with 10 mg of dosage when compared to control dogs [98,99]. In a clinical, randomized, controlled, and prospective study [79], 60 client-owned dogs were randomly allocated to the R group (n = 30, robenacoxib 1 mg/kg/day) and the UC-II group (UC-II 1 tablet (40 mg)/day) for a 30 days study.…”
Section: Uc-ii Usage In Dogsmentioning
confidence: 87%
“…Type II collagen is available in the form of denatured and undenatured types in the market, while previous studies involved undenatured type II collagen, modulating joint health in OA and RA (5,7,15). NEXT-2 has been also examined about safety and efficacy on animal (11)(12)(13). We expected that NEXT-II could be higher in human utilization in respect to its high water-solubility in nature.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed water soluble undenatured type II collagen (NEXT-II ® ) in light of potential delivery in the liquid form. Recently, we reported safety and efficacy in NEXT-II ® on mice, rats and, dogs (11)(12)(13). In the clinical pilot study, the aim is to evaluate the efficacy and safety of NEXT-II ® in subjects who have health concerns of their knee joints.…”
Section: Introductionmentioning
confidence: 99%